“God Helps the Red Army”: The History of the Canonization of Saint Luke the Blessed Surgeon and Alexander of Munich in the Context of Politics of Memory - Daniil Anikin (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения)
Introduction. The purpose of the article is to analyze the canonization practices of Luke of Crimea and Alexander of Munich in the context of using their images in commemorative practices dedicated to the Second World War in the post-Soviet period. The relevance of the study is determined by the increasing role of religious actors in the commemoration of the Second World War and the need for a historical and political analysis of the mechanisms and practices of their activities. Methods and materials. Research methods include a comparative analysis of diocesan periodicals, decisions of the Synodal Commission for the Canonization of Saints, and reports on the topics affected in the media, as well as actor analysis (A.I. Miller), which involves identifying the political interests of religious actors and the context for their implementation. The materials are the lives of Saints Luke the Blessed Surgeon and Alexander of Munich, diocesan periodicals, and media reports. Particular attention during the study is given to regional specifics, enabling the identification of features in the representation of the image of saints within local commemorative practices. Analysis. The history of the canonization of Saint Luke the Blessed Surgeon demonstrates that his evolution from locally revered to church saints is associated primarily with the active use of the image as the spiritual patron saint of doctors, as well as with the coincidence of the anniversary of the acquisition of his relics with the date of the reunification of Crimea and Russia. The military connotations of his image are secondary and appear only in the emergence of local discourses that actively use similar aspects of his biography. The canonization of Alexander of Munich takes place in the context of the reunification of the Russian Orthodox Church and ROCOR, which makes it necessary to search for non-conflict common images of the past. Results. A feature of the politics of memory in the field of religious memorials of the Second World War is the weak use of images of direct participants due to both canonical and political factors that make it difficult to form consistent images.